Effects of Fun Thinkers Book Media on Fourth-Grade Stu-dents’ Critical Thinking and Creativity in IPAS Learning - Sri Wahyuni; Rahmawati Rahmawati; Nurdin Nurdin (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to determine the effect of using the Fun Thinkers Book learning media on critical thinking skills and learning creativity in IPAS among fourth-grade students of SDI Bontobu’ne, Bajeng District, Gowa Regency. This study employed a quantitative approach with a quasi-experimental design using the One Group Pretest–Posttest Design. The research subjects consisted of 21 fourth-grade students selected through purposive sampling. Data were collected using critical thinking tests, learning creativity questionnaires, and student activity observation sheets. Data analysis was conducted using descriptive and inferential statistics with SPSS version 27, including normality tests, homogeneity tests, t-tests, simple linear regression, and MANOVA tests.The results indicate an improvement in students’ critical thinking skills and learning creativity after the implementation of the Fun Thinkers Book learning media. The t-test results show a significance value less than 0.05, indicating a significant effect of the Fun Thinkers Book on students’ critical thinking skills and learning creativity. Furthermore, the MANOVA results reveal that the use of the Fun Thinkers Book has a simultaneous effect on both critical thinking skills and learning creativity in IPAS. Therefore, the Fun Thinkers Book learning media is effective for enhancing critical thinking skills and learning creativity among elementary school students..